"Impact of Covid on supply chain of Volkswagen AG and its implication on creating the strategy for after Covid future" - Hünefeld, Lukas; Pichanič, Mikuláš, 1942-; Hanzlíček, David; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
This thesis deals with the analysis of the impact of Covid-19 on the supply chain management of Volkswagen AG. The goal is to derive meaningful implications to give strategic recommendations for the future planning of supply chain management of Volkswagen AG. By analyzing the structure of global supply chains, as well as trends, influences, uncertainties affecting the automotive industry and the company in particular, valuable insights to processes are gained useful for the predication/estimation of the future. The output of the thesis are specific scenarios of the future, that were created under the TAIDA framework. Additional input was provided through interviews with supply chain experts and industry professionals. Key findings are the identification of drivers for the structural change of the automotive industry, as well as mitigation and response practices in supply chain management in regard to supply chain disruptions.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses